God’s Truth: The Foundation of Existence in the Old Testament and Implications for the Church’s Mission - Ndona, Yakobus; Ginting, Pulumun Peterus; Siagian, Liber; Ginting, Elisa Br (Evangelikal: Jurnal Teologi Injili dan Pembinaan Warga Jemaat, 2024)
This article talks about the truth of God as the foundation of the existence of Judaism. The article aims to reveal the Jewish understanding of the truth of God that underlies the existence and continuity of Christianity. The study uses a descriptive qualitative method through literary analysis. The primary data for the study are texts from the Old Testament related to the truth of God and their connections in various texts of the New Testament. The selected texts are then analyzed using Dilthey's hermeneutic circle and Gadamer's horizon fusion techniques. The results of the analysis show that the understanding of the truth of God in Judaism is centered on God's faithfulness to the covenant, but due to Israel's acute violation, the concept of truth shifted towards God's never-ending love and faithfulness. This understanding has a dimension of continuity in the New Testament and implications for the mission of the Church. This research helps readers gain an in-depth understanding that enriches evangelical theological research, helping to deepen understanding of God's character, nature, and plan in human salvation history. Through in-depth research, the church can also discover continuity between the Old and New Testaments to better understand how God's message and mission.